Visual inspection on cervix with acetic acid and Lugol’s iodine as a screening tool in detection of carcinoma cervix - D., Rita; R., Soumya; S., Pushpalatha V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Cervical cancer is a preventable and curable disease. In Indian women cervical malignancy accounts for 26.1–43.8% of all cancers. Visual inspection with acetic acid (VIA) or visual inspection with Lugol’s iodine (VILI) are considered to be a promising screening tools alternative to cervical cytology for primary cervical cancer screening in low resource setting. The purpose of the study is to evaluate VIA and VILI as cervical cancer screening tools in low resource setting; and to compare the efficacy of VIA and VILI in early detection of cancer cervix via colposcopy. Methods: The clinical study was conducted on 80 gynecological patients with history of heavy menstrual bleed and post-coital bleeding are included in study. Unmarried women patients, and active vaginal bleeding, were excluded. A biopsy was taken in patients with abnormal findings or suspicious findings of VIA/VILI. Results: In the present study, sensitivity of VIA and VILI is 90% and 50% respectively, specificity of VIA and VILI is 98.57% and 100% respectively, positive predictive value of VIA and VILI are 90%, 100% respectively, negative predictive value of VIA and VILI are 98.57% and 93.3% respectively with biopsy as the reference standard. Conclusions: It is concluded that VIA and VILI are good screening test in low resource setting as it can used in strategy of see and treat and screen and treat since there is low compliance of follow up of patients.